INHERITANCE AND ENLIGHTENMENT OF SUSTAINABLE HUMAN SETTLEMENTS UNDER THE TAOIST HOLISTIC VIEW - Qi, Luhui (Journal of Dharma, 2022)
Taoism and the sustainable development of human settlements have many things in common. This article first explains the thinking characteristics under the Taoist holistic view from two perspectives: i. individuals and countries, and ii. nature and society. And then, it expounds on the unique values formed under the Taoist holistic view through the ontology, methodology, and values of Taoism. Next, it elaborates on the relation of Taoism and the sustainable development of contemporary human settlements to show the transcendence and forward-looking nature of Chinese Taoist thinking. Finally, it analyses the intrinsic holistic value and China’s ‘community of life’ theory to show the inheritance and development of Taoism in contemporary times.